Schlieren-based temperature measurement inside the cylinder of an optical spark ignition and homogeneous charge compression ignition engine - Aleiferis, Pavlos G.; Charalambides, Alexandros G.; Hardalupas, Yannis; Soulopoulos, Nikolaos; Taylor, A. M. K. P.; Urata, Yunichi (My University, 2015)
Schlieren [Schlieren and Shadowgraphy Techniques (McGraw-Hill, 2001); Optics of Flames (Butterworths, 1963)] is a non-intrusive technique that can be used to detect density variations in a medium, and thus, under constant pressure and mixture concentration conditions, measure whole-field temperature distributions. The objective of the current work was to design a schlieren system to measure line-of-sight (LOS)-averaged temperature distribution with the final aim to determine the temperature distribution inside the cylinder of internal combustion (IC) engines. In a preliminary step, we assess theoretically the errors arising from the data reduction used to determine temperature from a schlieren measurement and find that the total error, random and systematic, is less than 3% for typical conditions encountered in the present experiments. A Z-type, curved-mirror schlieren system was used to measure the temperature distribution from a hot air jet in an open air environment in order to evaluate the method. Using the Abel transform, the radial distribution of the temperature was reconstructed from the LOS measurements. There was good agreement in the peak temperature between the reconstructed schlieren and thermocouple measurements. Experiments were then conducted in a four-stroke, single-cylinder, optical spark ignition engine with a four-valve, pentroof-type cylinder head to measure the temperature distribution of the reaction zone of an iso-octane-air mixture. The engine optical windows were designed to produce parallel rays and allow accurate application of the technique. The feasibility of the method to measure temperature distributions in IC engines was evaluated with simulations of the deflection angle combined with equilibrium chemistry calculations that estimated the temperature of the reaction zone at the position of maximum ray deflection as recorded in a schlieren image. Further simulations showed that the effects of exhaust gas recirculation and air-to-fuel ratio on the schlieren images were minimal under engine conditions compared to the temperature effect. At 20 crank angle degrees before top dead center (i.e., 20 crank angle degrees after ignition timing), the measured temperature of the flame front was in agreement with the simulations (730-1320 K depending on the shape of the flame front). Furthermore, the schlieren images identified the presence of hot gases ahead of the reaction zone due to diffusion and showed that there were no hot spots in the unburned mixture.
Keywords: Schlieren and Shadowgraphy Techniques; Optics of Flames; Density variations; Cconstant pressure